Disease, culture contact, and tribals - Vyas, N. N.; Mann, Rann Singh, 1936- (Tribe (Udaipur, India), 1980)
Contributed articles on tuberculosis and venereal diseases among the socially and economically underprivileged people in Rajasthan.